Impacto da suplementação de micronutrientes em cervejas e análise de voláteis em cervejas e lúpulos por cromatografia gasosa bidimensional abrangente - Glaucimar Alex Passos de Resende (2024)
The study of beers and their raw materials is of utmost importance for the scientific, technological, and commercial development of this beverage. Thus, this thesis addresses three works in this aspect. The first work of this thesis involved the analysis of twelve parameters in blond ale beers with the addition of 7.5%, 12.5%, and 17.5% of the recommended daily intake value (IDR) with molybdenum, selenium, and chromium salts. Among the results found, there was an increase in ethanol production due to the supplementation with micronutrients, leading to higher carbohydrate consumption in the presence of chromium and a general influence on the volatile acidity of the samples. There were physicochemical differences in the studied beers demonstrated by the influences from the use of chemometric tools (principal component analysis - PCA and hierarchical cluster analysis - HCA), as well as different types of correlations with these salts. Through these tools, it was possible to verify the greatest similarity between control samples and those with molybdenum supplementation, as well as the relationship of vicinal diketones and color for chromium supplementation. As for the second work, the volatile behaviors were studied by adding commercial selenium and chromium micronutrients to the brewing wort during the production of four types of beer (Au, AuH, IPA, and St). Volatiles were determined via solid-phase microextraction by headspace (HS-SPME) and comprehensive two-dimensional gas chromatography coupled to mass spectrometry (GC×GC-MS). Multimodal principal component analysis (MPCA) was used to explore possible alterations due to the addition of micronutrients, with alterations mainly observed with chromium addition and influence on the alcohols present in the samples. In addition, individual models for Au and AuH beers again demonstrate differences in the volatile profile by MPCA, as well as differences for selenium with compounds like octanoic acid. The third work involved the analysis of hop metabolites by HS-SPME-GC×GC-MS. The best SPME extraction condition under the studied conditions occurred with the use of DVB/PDMS fiber (65 µm), 500 mg of ground hops, and extraction time of 40 minutes at 50 °C. Five hop varieties were studied globally: Azzaca, Cascade, Enigma, Loral, and Zappa. Comparing GC-MS and GC×GC-MS, there was an improvement in peak detection with an increase of up to 316.8%. Thus, 137 compounds of 10 different classes were tentatively identified, with values between 87.6% and 96.9% of the total peak area in the chromatographic areas. Through PCA for the identified compounds, PCA and HCA for the classes of compounds, similarities were found between Zappa and Cascade, and Azacca and Loral. With these works, it is concluded that the supplementation of micronutrients as well as the use of HS-SPME-GC×GC for hop analysis add good prospects for brewing technology.